Principles of anatomy and physiology organization, support and movement, and control systems of the human body - Tortora, Gerard J.; Derrickson, Bryan H. (John Wiley & Sons, 2009)
This edition of 'Principles of Anatomy and Physiology' maintains the superb balance between structure and function. It continues to emphasize the correlations between normal physiology and pathophysiology, normal anatomy and pathology, and homeostasis and homeostatic imbalances. The acclaimed illustration program is also even better along with the redevelopment of many of the figures depicting the toughest topics to grasp.